MODEL PENILAIAN HASIL BELAJAR DAN KARAKTER - Heryanto Heryanto Heryanto (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2018)
The purpose of this article is to provide an overview of student learning and character assessment. The assessment of student learning has been focus more on mastery of material, but less attention to aspects of character. Whereas in education has two dimensions of purpose, namely to be smart and good morals. Intelligence has related to cognitive, while character has related to affective. Through this study, has expected to obtain a model of assessment that involves cognitive and affective aspects in an integrated manner. The method of study has done in compiling the article through literature study, i.e. studying the theory or opinion relating to student learning assessment. Based on this study, it concluded that: (1) Assessment of learning and character carried out independently. (2) Teachers face constraints assessing the character of students. (3) There are a number of interventions to the teacher's assessment; (4) Collaborative assessment of learning and character makes it easier for teachers and schools to make responsible decisions. (5) Assessment of learning has a positive implication on the formation of student character or otherwise.